ETHNOMATHEMATICS OF KAWUNG SOLO BATIK AS A LEARNING MEDIA FOR STREAM-BASED GEOMETRY TRANSFORMATION - TOHA, ANDI MUHAMMAD; SEPTI, ALEZA DWI; ASTUTI, WIWIN; BISRI, MOH. (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2024)
This research is a literature study assessment that uses exploratory techniques with an ethnographic approach. The aim of this research is to explore Solo kawung batik as a learning medium for geometric transformations. The form of batik called "kawung batik" is in the form of geometric circles that resemble kawung fruit, which is also known as kolang-kaling or sugar palm. The message contained in the kawung motif is that a person must be an individual who is superior, good, and helps others. The results of this research show that 1) Kawung motifs have periodic repeating patterns at certain intervals, 2) Kawung batik contains symmetrical patterns, concepts of congruence and congruence, 3) In Kawung batik motifs there are elements of geometric transformation such as mirroring, rotation and shifting. which can later be used as a mathematics learning medium as is the aim of this research. This learning media is designed to integrate elements of Science, Technology, Reading, Engineering, Arts, and Mathematics (STREAM), so that it can combine literacy skills, art aesthetics, and mathematics in more comprehensive learning. ABSTRAKPenelitian ini merupakan penelitian studi kepustakaan yang menggunakan teknik eksploratif dengan pendekatan etnografi. Tujuan penelitian ini adalah untuk mengeksplorasi batik kawung Solo sebagai media pembelajaran transformasi geometri. Bentuk batik yang disebut dengan “batik kawung” adalah berbentuk lingkaran-lingkaran geometris yang menyerupai buah kawung, disebut juga kolang-kaling atau enau. Pesan yang terkandung dalam motif kawung adalah seseorang harus menjadi individu yang unggul, baik, dan suka membantu orang lain. Hasil penelitian menunjukkan bahwa 1) Motif Kawung mempunyai pola berulang secara periodik dalam interval tertentu, 2) Batik Kawung mengandung pola simetris, konsep kongruensi dan kongruensi, 3) Pada motif batik Kawung terdapat unsur transformasi geometri seperti pencerminan, perputaran. dan bergeser. yang nantinya dapat digunakan sebagai media pembelajaran matematika sebagaimana tujuan penelitian ini. Media pembelajaran ini dirancang untuk mengintegrasikan unsur Science, Technology, Reading, Engineering, Arts, and Mathematics (STREAM), sehingga dapat memadukan keterampilan literasi, estetika seni, dan matematika dalam pembelajaran yang lebih komprehensif.